Caught in the Act: How the U.S. Lacey Act Can Hamper the Fight Against Cyanide Fishing in Tropical Coral Reefs. Issue 6 (13th February 2014) - Calado, Ricardo; Leal, Miguel C.; Vaz, Marcela C.M.; Brown, Chris; Rosa, Rui; Stevenson, Todd C.; Cooper, Cara H.; Tissot, Brian N.; Li, Ya‐Wei; Thornhill, Daniel J.
Abstract Cyanide fishing is one of the most destructive techniques employed to collect live reef fish. While national laws of most source countries ban this practice, cyanide is still widely employed to capture live reef fish for human consumption and marine aquariums. The United States is one of the largest importers of live reef fish, and the implementation of new approaches to screen for fish caught with cyanide is urgently needed. A fast and reliable noninvasive and nondestructive approach to screen live reef fish for cyanide poisoning was recently developed, yet deployment of this test may be obstructed by U.S. law. The Lacey Act prohibits the import, export, transport, and acquisition in interstate or international commerce of fish taken in violation of any foreign law. Therefore, if a fish tests positive for cyanide poisoning, the testers could expose themselves to liability for potential Lacey Act violations, as they are "knowingly" engaging in an illegal act. To eliminate this disincentive, the U.S. government should help conservationists develop protocols on how to test for cyanide poisoning without violating the Lacey Act.